Examining spatial and social characteristics of customary trees owned by villagers on public forestlands in Jharkhand, India - Sabyasachi Kar; Roger Lowe, III; Ashok Kumar Chaudhary; Puneet Dwivedi (Trees, Forests and People)
Tree ownership is typically tied to land ownership in many societies worldwide. Still, in India, tribal communities have customary ownership over trees in public forestlands, raising questions about what those trees are, where they are located, their characteristics, and whether socioeconomic factors influence their distribution and density. To address these questions, we conducted household interviews and a Global Positioning System (GPS) mapping in Sahritola, a village in the State of Jharkhand, India. We employed Kruskal Wallis, Spearman correlation, and Moran's Index to analyze the collected data. The villagers have been protecting and managing over 18,000 trees in public forestlands, including species such as asan (Terminalia tomentosa), sal (Shorea robusta), and mahua (Madhuca longifolia). Over 80 % of those trees are under individual ownership, while around 20 % are under shared ownership. Additionally, over 60 % of households owned between 100 and 500 trees. Customarily-owned tree species sharing similar characteristics (e.g., height, crown width, and diameter-at-breast-height) tend to cluster together. The number of customarily owned trees is influenced by their economic value and socioeconomic factors (e.g., religion, forestland, etc.). Additionally, the type of customary ownership (individual or shared) influences the characteristics of trees. This study could guide policymakers in potentially developing forest policies that consider the concept of customary tree ownership to promote sustainable management of forest resources in India and beyond.